Quality of Life in Osteoarthritis: Relationship with Demographic and Clinical Variables - Seçilay Güneş; Beyza Doğanay Erdoğan; Şehim Kutlay; Ayşe Adile Küçükdeveci (Türk Osteoporoz Dergisi)

(untitled)
Objective:To investigate the relationship of quality of life (QoL) with demographic and clinical variables in osteoarthritis (OA).Materials and Methods:QoL of 156 patients (79.5% female) with the knee, hip, foot, and/or hand OA was assessed by the OAQoL scale. Zero-10 numeric rating scale (NRS) for pain severity, Health Assessment Questionnaire (HAQ) for general physical disability, Western Ontario and McMaster Universities Index of Osteoarthritis (WOMAC) for knee/hip disability, and the Nottingham Health Profile (NHP) for health status were also completed by patients.Results:Mean age was 56±10 and mean disease duration 7.2±6.4 years. There were moderate-to-strong significant correlations (r=0.50-0.70) between QoL and HAQ, WOMAC-pain, WOMAC-function, WOMAC-stiffness, NHP-physical mobility, and NHP-energy. QoL was not related to the number of joints affected by osteoarthritis. A linear regression model was performed to determine the factors that together explain the variability in QoL. Potential variables which found statistically significant in univariate linear regression analyses were used in a stepwise regression procedure to select the final multivariate model. The final model included pain (NRS), HAQ, NHP-energy, and NHP-social isolation with an adjusted R2 of 0.645.Conclusion:Pain, physical function, fatigue, and social isolation have been found to be the predictors of QoL in this osteoarthritis patient group, explaining 64.5% of the variance.